Análise da trajetória da Associação Brasileira de Enfermagem - Seção Ceará - André Ribeiro de Castro; Silvia Maria Nobrega-Therrien; Maria Irismar de Almeida; Daniele Vasconcelos Fernandes Vieira; Francisca Gomes Montesuma (Universidade Federal do Ceará, 2017)
Objective: to describe the trajectory of the Brazilian Nursing Association . Methods: documental research with data obtained mainly from minutes of meetings of the Brazilian Nursing Association - Ceará Section. A book report was produced, with quantitative and qualitative surveys of recurrent terms and issues in the minutes. Data were triangulated and interpreted into categories. Results: information concerning the association were divided into five categories, which exposed the profile of the boards and their priorities in the nursing discussion in Ceará, highlighting challenges, struggles and positions about nursing education, and encouraging the production and scientific dissemination, contextualized in the social and political conditions. Conclusion: the Brazilian Nursing Association - Ceará Section is emblematic in building the history of the profession in Ceará, because it brings reflections about the importance of associations to strengthen and bring visibility to the class struggles, the qualification of education and the expansion of scientific production.